Ronald Dvorkin’s political and legal ideas – general-civilization standard of legal life - Kravchuk, Mykola; Kravtsova, Nataliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2019)
In this article the basic legal ideas of Ronald Dworkin are reflected. An analysis of the scientific works of the innovator of the law is carried out. The relation of the scientist to other philosophical and legal concepts is clarified and on this basis his definitive approaches to the basic categories of legal matter are distinguished. The article outlines the basic political and legal views of the scientist, who form the civilization standard of legal life. In particular, the scientist's views on the correlation of law with morality, politics, economy, and religion were evaluated. The article reflects four stages of R. Dworkin's scientific work and states that the work of the innovator was directly and indirectly influenced by the works of many scientists of the time, including Herbert Garth, John Rawls, Isaiah Berlin. The authors' main conclusions are as follows: first, the Ronald Dworkin doctrine is characterized by three main areas of scientific exploration: the concept of law, the doctrine of justice, the theory of values. Definition of vectors of scientific researches of a scientist is directly connected with the essential socio-cultural processes that have occurred during his activity. Second, Ronald Dworkin has based his theory in each of these areas most often on the basis of counter-argumentation against other theorists. The ideological inheritance united in a single general concept is subordinated to uniform principles. Third, when analyzing and evaluating the theoretical work of Ronald Dworkin, it should be noted that most of his publications were not originally intended as independent works, but were collections of previously published journal articles. The scientist has often rethought his ideas earlier, bringing new meaning to them. His legal ideas went beyond law; he considered it expedient and useful to be able to judge the law, taking into account the content and nature of politics and morality.